PENGARUH PROMOSI TERHADAP SIKAP PASIEN RS PKU MUHAMMADIYAH BANTUL - Sari Dwi Astuti (2012)
Background : With a lot of hospital around Bantul, to be known by society, the hospital should be doing a promotion including PKU Muhammadiyah Hospital of Bantul. Promotion is very useful to give an information to society about the excellence and services that offered by hospital, in hope that hospital could be the reference of society to get treatment and medical helps. Methode : This study used quantitative and descriptive with cross sectional approach. The population is all outpatient patien